Flavonoit glycosit từ cây cách thư Poilanei Fissistigma poilanei (Ast) Tsiang & P. T. Li], họ na (Annonaceae) - Thanh thuỷ, Trần Thị; Quân, Trần Đức; Hoàng Anh, Nguyễn Thị; Sung, Trần Văn (Vietnam Journal of Chemistry, 2014)
Three flavonoid glycosides: (2R,3R)-3’,4’,5,7-tetrahydroxydihydroflavonol-3-O-a-L rhamnopyranoside (1), (+)-catechin 3-O-a-L-rhamnopyranoside (2) and quercetine 3,7 dimethoxy-3’-O-a-L-rhamnopyranosyl-(1®2)-b-D-glucopyranoside (3) were isolated from the ethyl acetate extract of Fissistigma poilanei. Their structures were elucidated by analysis of MS and NMR spectra and comparison with the published data.